2019
DOI: 10.5935/1806-6054.20190013
|View full text |Cite
|
Sign up to set email alerts
|

Primary small cell carcinoma of the thyroid: a case report

Abstract: The diagnosis of cervical mass is a challenge due to the wide variety of benign and malignant etiologies. Extrapulmonary small cell carcinomas (EPSCC) are rare entities, and those tumours arising as a primary cervical, especially in the thyroid gland, are exceedingly rare. As others small cell neuroendocrine carcinomas, the disease has an aggressive behavior. This case report is about a 40-years-old female patient admitted to the Hospital Felício Rocho, with airway compression caused by a cervical mass origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 3 publications
(3 reference statements)
0
3
0
Order By: Relevance
“…In the 4th edition of WHO classification of thyroid tumors, high-grade neuroendocrine carcinomas are not listed as a distinctive type ( 2 ) and the fact that this tumor exhibited neuroendocrine differentiation, meant that calcitonin-negative medullary thyroid carcinoma (MTC) needed to be considered in the differential diagnosis. However, the tumor had no histological characteristics for MTC, and the morphological characteristics, such as minimal cytoplasm, nuclear molding, high mitotic figure, and immunohistochemical features such as being positive for CD56 and synaptophysin were similar to those of lung SCC ( 9 ). Sporadic MTCs are well-differentiated and locally aggressive tumors ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In the 4th edition of WHO classification of thyroid tumors, high-grade neuroendocrine carcinomas are not listed as a distinctive type ( 2 ) and the fact that this tumor exhibited neuroendocrine differentiation, meant that calcitonin-negative medullary thyroid carcinoma (MTC) needed to be considered in the differential diagnosis. However, the tumor had no histological characteristics for MTC, and the morphological characteristics, such as minimal cytoplasm, nuclear molding, high mitotic figure, and immunohistochemical features such as being positive for CD56 and synaptophysin were similar to those of lung SCC ( 9 ). Sporadic MTCs are well-differentiated and locally aggressive tumors ( 12 ).…”
Section: Discussionmentioning
confidence: 97%
“…Primary SCCs have been intermittently reported previously, but most of them have presented as low-grade lymphoma or PDTC following immunohistochemical evaluation. Approximately 6–7 cases of primary small cell thyroid carcinomas (SCTCs) meeting the diagnostic criteria for small cell carcinoma have been reported in previous years ( 3 , 4 , 5 , 9 , 11 ). Eusebi et al ( 5 ) reported two cases of SCC that met the morphologic and immunohistochemical criteria for SCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation